Epidermotropic pagetoid spread and squamous cell carcinoma in situ in the overlying epidermis of Merkel cell carcinoma - Toshiyuki Yamamoto (Our Dermatology Online, 2014)
A 71-year-old female visited the Department of Dermatology at Tokyo Metropolitan Bokuto Hospital, complaining of a nodule in the face. She was diagnosed as Merkel cell carcinoma by a skin biopsy in another clinic, and referred to our hospital for operation. A physical examination revealed a dome-shaped reddish nodule, sized 1-cm in diameter, in the center of the left cheek. Cervical lymph nodes were not palpable.